Step up to triple therapy versus switch to dual bronchodilator therapy in patients with COPD on an inhaled corticosteroid/long-acting β2-agonist: post-hoc analyses of KRONOS - Dave Singh; Mona Bafadhel; Niki Arya; Jonathan Marshall; Himanshu Parikh; Dobrawa Kisielewicz; Charlotta Movitz; Karin Bowen; Mehul Patel (Respiratory Research)
Abstract Background In people with chronic obstructive pulmonary disease (COPD) on inhaled corticosteroid/long-acting β2-agonist (ICS/LABA) therapy, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommends stepping up to ICS/long-acting muscarinic antagonist (LAMA)/long-acting β2-agonist (LABA) in those with exacerbations or switching to LAMA/LABA in those with major symptoms. However, the effect of stepping up to ICS/LAMA/LABA versus switching to LAMA/LABA on exacerbation risk is unclear. This analysis evaluated the effect of escalating to ICS/LAMA/LABA versus switching to LAMA/LABA or staying on ICS/LABA on lung function and exacerbation rates in symptomatic individuals with COPD without a recent exacerbation history from KRONOS. Methods In KRONOS (NCT02497001), symptomatic participants with moderate-to-very severe COPD (exacerbations in the prior year were not required for inclusion) were randomized to budesonide/glycopyrronium/formoterol fumarate dihydrate 320/14.4/10 μg (BGF), glycopyrronium/formoterol fumarate dihydrate 14.4/10 μg (GFF), budesonide/formoterol fumarate dihydrate 320/10 μg (BFF) via metered-dose inhaler, or budesonide/formoterol fumarate dihydrate 400/12 μg via dry-powder inhaler (BUD/FORM) for 24 weeks. In participants without a recent exacerbation history on ICS/LABA in the 30 days before screening, morning pre-dose trough FEV1 change from baseline and moderate/severe exacerbation rates over 24 weeks were analyzed post-hoc using linear repeated measures models and negative binomial regression, respectively, and participants escalated to ICS/LAMA/LABA (BGF) were compared with those switching to LAMA/LABA (GFF) or staying on ICS/LABA (BFF or BUD/FORM). Results On stepping up to BGF, least square means (95% confidence interval [CI]) differences for morning pre-dose trough FEV1 change from baseline over 24 weeks was similar versus switching to GFF (12 [–21, 44] mL) but greater versus staying on ICS/LABA (BGF vs. BFF, 106 [64, 148] mL; BGF vs. BUD/FORM, 55 [12, 97] mL). Moderate/severe exacerbations were experienced by participants in all treatment arms (BGF, 14.9%; GFF, 24.0%; BFF 17.6%; BUD/FORM, 21.2%). Exacerbation risk was reduced when stepping up to BGF versus switching to GFF (rate ratio [95% CI]: 0.57 [0.35, 0.94]); rate ratios (95% CI) for BGF versus remaining on ICS/LABA were 0.93 (0.47, 1.82) with BFF and 0.62 (0.33, 1.18) with BUD/FORM. Conclusions People with symptomatic COPD and no recent exacerbation history previously on ICS/LABA had reduced exacerbation risk after escalating to ICS/LAMA/LABA versus switching to LAMA/LABA, and improved lung function versus staying on ICS/LABA. Trial registration ClinicalTrials.gov registry number NCT02497001 (registration date, 7 July 2015).